In Search of Social Democracy : Responses to Crisis and Modernisation - Callaghan, John (John T.) (Book collections on Project MUSE., 2009)
The search for social democracy has not been an easy one over the last three decades. The economic crisis of the 1970s, and the consequent rise of neo-liberalism, confronted social democrats with difficult new circumstances: tax-resistant electorates, the globalisation of capital and Western deindustrialisation. In response, a new bout of ideological revisionism consumed social democratic parties. But did this revisionism simply amount to a neo-liberalisation of the Left or did it propose a recognisably social democratic agenda? Were these ideological adaptations the only feasible ones or were there other forms of modernisation that might have yielded greater strategic dividends for the Left? Why did some social democratic parties feel it necessary to take their revisionism much further than others? In search of social democracy brings together prominent scholars of social democracy to address these questions. Focusing on the social democratic heartland of Western Europe (although Australia and the United States also figure in the analysis), it gives the first detailed assessment of how the new social democratic revisionism has fared in government. The book begins by considering the underlying causes of the end of social democracy's golden age and the magnitude of the challenges faced by social democratic parties after the 1970s. It then proceeds to examine detailed case studies of how particular social democratic parties responded to this changed political terrain. Finally, it contributes to a broader conversation about the future of social democracy by considering ways in which the political thought of 'third way' social democracy might be radicalised for the twenty-first century. The contributors offer a variety of perspectives -- some are sceptical of social democracy's prospects, others more sanguine; some supportive of the performance of social democratic parties in government, others bitingly critical. But they are united by the conviction that the themes addressed in this book are crucial to understanding the current politics of the industrialised world and, in particular, to determining the feasibility of more egalitarian and democratic social outcomes than have been possible so far in the era of neo-liberalism.